Metabolic syndrome in the rural population of Wardha, Central India: An exploratory factor analysis - Pradeep R Deshmukh; Pranita Kamble; Kalyan Goswami; Neelam Garg (Wolters Kluwer Medknow Publications, 2013)
Background and Objectives: Metabolic syndrome - a plausible precondition for type II diabetes and cardiovascular diseases is also on rise. To understand the mechanistic complexity of metabolic syndrome it is imperative to study the specific contribution of the determinants of metabolic syndrome. Such study can help to identify the most significant factor which may be of use in early detection as well as prevention efforts. Such information is scarcely available from India and especially from rural India. Hence, the present study was undertaken to explore for such factor which might be considered crucial for development of such pathogenesis particularly in rural population of Wardha. Methods: A cross-sectional study comprising of 300 subjects was carried out in rural area of Primary Health Center, attached to medical college with approximate 31,000 populations. The anthropometric parameters such as height, weight, waist circumference were measured. Overnight fasting samples were collected for lipid profile (total cholesterol, triglyceride, high density lipoproteins, low density lipoproteins, very low density lipoproteins) and fasting blood glucose levels. The National Cholesterol Education Programme Adult Treatment Panel, ATP-III guidelines were used to categorize the study subjects. As many of the variables are highly intercorrelated, exploratory factor analysis was carried out to reduce the data to a smaller number of independent factors that accounts for the most of the variances in the data. Principal component analysis was used as a method of extraction. Results: For both sexes, three factors were extracted accounting for about 71% variance in the measured variables. An adiposity factor which accounted for highest explained variance (28%), was the initial factor extracted. It was loaded positively by waist circumference, triglyceride, and very low density lipoprotein and negatively loaded by high density lipoprotein. Second factor extracted was a cholesterol factor which explained about 20% variance. It was positively loaded by total cholesterol and low density lipoprotein. Blood pressure factor was third to be extracted which again explained about 20% variance. It was positively loaded by systolic and diastolic blood pressure. Interpretation and Conclusion: The results clearly indicate the significance of visceral adiposity over the obesity in general or simple abdominal obesity measured anthropometrically as a pathogenic determinant of the metabolic syndrome. The most consistent factor has been found to be dyslipidemia which explained major share of the observed variance and the most significant load of this factor being rested on triglyceride and the VLDL level. Hence, we conclude measurement of triglyceride might be a rewarding screening parameter for assessment of cardio-metabolic risk in general populace and warrants a large scale study focusing into this issue.